Influential literature in applied sports biomechanics - Knudson, D.; Ostarello, J. (ISBS - Conference Proceedings Archive (Konstanz), 2010)
This study documented the perception of prestige of applied sports biomechanics journals, as well as influential articles and books. Recent ISBS members were surveyed to rate the quality/prestige of 35 journals. Descriptive statistics of ratings were calculated for respondents and correlated with the 2008 impact factor (IF) reported in the Journal Citation Reports. Mean ratings showed that international perception of influential journals were weakly (r = 0.48) correlated with the IF. These results confirm previous studies that the IF is a poor index for evaluating the influence of journals publishing applied sports biomechanics research, and there was considerable diversity among the respondent's nominations of the most influential books and articles in the field.